Monitoring of biotransformation of hop aroma compounds in an in vitro digestion model - Heinlein, Anja; Büttner, Andrea (Food & Function, 2012)
An in vitro digestion procedure followed by gas chromatography-mass spectrometry analysis has been applied to assess the stability of aroma compounds from hop oil in the human gastrointestinal tract. Hop oil is used in phytotherapy as a sedative, yet the bioactive substances responsible for this effect have not been conclusively clarified. Therefore, the focus of this study was placed on hop aroma substances that: (i) have been previously described to possess sedative properties, (ii) are suspected to have these properties due to structural features, or (iii) that are present in hop oil in high concentrations. While some compounds remained unchanged under the simulated physiological conditions, others underwent transformations to a great extent. Particularly interesting was the formation of α-terpineol and linalool from several different aroma compounds. α-Terpineol has been previously described as a bioactive compound with anti-inflammatory properties. Linalool is a well-known sedative compound and its formation during digestion could enhance the sedative effect of hop oil. The results of this study show that gastrointestinal processes can modulate the chemical composition of ingested aroma constituents and might even influence the bioactivity of essential oils. This journal is © 2012 The Royal Society of Chemistry.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.monito